Molecular cloning and characterization of nitric oxide associated 1 transcript from oil palm (Elaeis guineensis Jacq.) and its recombinant protein produced from prokaryotic system - Kwan, Yee Min (2014)
Basal stem rot (BSR) disease in oil palm is caused by Ganoderma fungi. It has resulted in severe economic loss, and the current disease management strategies were of low effectiveness. Nitric oxide (NO) is a ubiquitous signaling molecule which plays a role in plant disease resistance against pathogens. Nitric oxide associated 1 (NOA1) protein is implicated in NO biosynthesis and NO associated plant defense responses against pathogen infection. This study was conducted to isolate a transcript encoding NOA1 protein from oil palm (designated as EgNOA1) and examine the guanosine triphosphate (GTP) hydrolysis activity of its recombinant protein obtained from Escherichia coli (E. coli). In addition, the expression profile of EgNOA1 in Ganoderma infected oil palm and its correlation with NO biosynthesis were investigated. The full length complementary DNA (cDNA) sequence of EgNOA1 was isolated by Rapid Amplification of cDNA Ends Polymerase Chain Reaction (RACE PCR). EgNOA1 has an open reading frame (ORF) of 1674 bp that encodes a polypeptide chain of 558 amino acid residues. EgNOA1 is a circularly permuted GTPase (cpGTPase) belonging to the YqeH subfamily with three characteristic domains- zinc binding domain (ZBD), circularly permuted GTPase (CPG) domain and C-terminal domain (CTD). The motif residues of the CPG domain arranged in the permuted order are G4 (TKID), G5 (SSK), G1 (GSANVGKS), G2 (T), and G3 (DTPG). Two recombinant proteins, a complete ORF of EgNOA1 (EgNOA1fl) and a deletion variant and a deletion variant and a deletion variant and a deletion variant and a deletion variant and a deletion variant and a deletion variant and a deletion variant and a deletion variant and a deletion variant and a deletion variant and a deletion variant and a deletion variant and a deletion variant and a deletion variant and a deletion variant and a deletion variant and a deletion variant and a deletion variant and a deletion variant (EgNOA1Δ99) without its 99 amino acids at the N-terminal end was produced in E. coli cells using the pET-32 Xa/LIC expression vector and verified by Western blot analysis. The hydrolysis of GTP to guanosine diphosphate (GDP) and inorganic phosphate ion catalyzed by the purified EgNOA1fl and EgNOA1Δ99 recombinant proteinproteinproteinproteinproteins was measured using was measured using was measured using was measured using was measured using was measured using was measured using was measured using was measured using was measured using was measured using was measured using was measured using was measured using was measured using was measured using was measured using was measured using the the the the malachite green assay. The purified EgNOA1Δ99 recombinant protein was protein was protein was protein was protein was protein was protein was protein was protein was protein was demonstrated to demonstrated to demonstrated to demonstrated to demonstrated to demonstrated to demonstrated to demonstrated to demonstrated to demonstrated to demonstrated to demonstrated to catalyze significantly higher release of GDP and phosphate ion compared to that of EgNOA1fl. Griess assay and quantitative real-time PCR (qPCR)was performed to examine the NO concentration and the expression of EgNOA1 respectively in Ganoderma-treated root tissue at 3, 7, 14, 21, 28, 56 and 96 days after inoculation (DAI). NO burst was detected at 14 DAI, and the transcript abundance of EgNOA1 was up-regulated at 96 DAI. In conclusion, the findings of this study have provided insights on EgNOA1 as a GTPase and its differential transcript regulation in oil palm root tissue when infected by Ganoderma.